Analisis Kemampuan Penalaran Matematis Siswa dalam Menyelesaikan Sistem Persamaan Linear Dua Variabel Berdasarkan Gaya Belajar - Aryanto, Aryanto; Gandung Sugita; Anggraini; Mustamin Idris (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to describe students' mathematical reasoning ability in solving story problems of two-variable linear equation system. The method used is qualitative with a descriptive approach. The results showed that; (1) students with visual learning styles understood the information well through graphs, but were less thorough in numerical manipulation and verbal instructions, causing calculation errors and mathematical modeling (2) auditorial students were able to understand the problem and plan the solution well, but were less thorough in calculations and had difficulty transferring information to mathematical form, resulting in incorrect answers, (3) kinesthetic students understood the problem and planned the solution, but experienced errors in calculations due to difficulty understanding abstract information, lack of accuracy, and difficulty focusing for a long time. Therefore, it can be concluded that the reasoning ability of 8th grade students of SMPK BK Palu is quite good, it just needs to increase the accuracy of the students themselves.   Keywords: Mathematical Reasoning, SPLDV, Learning Style.